2015
DOI: 10.1111/cei.12672
|View full text |Cite
|
Sign up to set email alerts
|

CD4 T cell differentiation in type 1 diabetes

Abstract: SummarySusceptibility to type 1 diabetes is associated strongly with human leucocyte antigen (HLA) genes, implicating T cells in disease pathogenesis. In humans, CD8 T cells predominantly infiltrate the islets, yet their activation and propagation probably requires CD4 T cell help. CD4 T cells can select from several differentiation fates following activation, and this choice has profound consequences for their subsequent cytokine production and migratory potential. In turn, these features dictate which other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
113
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(119 citation statements)
references
References 171 publications
1
113
0
1
Order By: Relevance
“…Interestingly, in autoimmune diseases, a separate population of T H cells, the T H 1/T H 17 cells that co-produce both IL-17 and IFN-γ, has been found [54] . Several studies have found an increased polarization of IL-17+ cells to produce IFN-γ in children with T1D compared with healthy controls [55,56] . Thus, the presence of T H 1/T H 17 cells could potentially be a hallmark of T1D, even if further investigation is required.…”
Section: The Il-23/il-17 Axismentioning
confidence: 99%
“…Interestingly, in autoimmune diseases, a separate population of T H cells, the T H 1/T H 17 cells that co-produce both IL-17 and IFN-γ, has been found [54] . Several studies have found an increased polarization of IL-17+ cells to produce IFN-γ in children with T1D compared with healthy controls [55,56] . Thus, the presence of T H 1/T H 17 cells could potentially be a hallmark of T1D, even if further investigation is required.…”
Section: The Il-23/il-17 Axismentioning
confidence: 99%
“…[H2] Involvement of TLRs T1DM is a well-established type 1 T helper (TH1) cell-mediated disease whereby pancreatic β cells are selectively injured and destroyed 29 . Many of the studies that have addressed the mechanisms of T1DM have mainly focused on the role of the adaptive immune system that is mediated by T lymphocytes.…”
Section: [H2] Inflammasomesmentioning
confidence: 99%
“…The role of CD8 1 T cells responding to ChgA autoantigen in the destruction of pancreatic islet b cells and diabetes development in NOD mice has not been documented. In NOD mice, both CD4 1 and CD8 1 T cells contribute to diabetes pathogenesis [8][9][10][11]. NOD mice deficient in major histocompatibility complex (MHC) class I molecules are resistant to diabetes development [12,13].…”
Section: Introductionmentioning
confidence: 99%